Birt‐Hogg‐Dubé syndrome‐associated renal cell carcinoma: Histopathological features and diagnostic conundrum. Issue 1 (17th December 2019) - Furuya, Mitsuko; Hasumi, Hisashi; Yao, Masahiro; Nagashima, Yoji
Abstract: Birt‐Hogg‐Dubé (BHD) syndrome is associated with the development of hereditary renal cell carcinoma (RCC) and is caused by a germline mutation in the folliculin gene. Most cases of BHD syndrome‐associated RCC (BHD‐RCC) are less aggressive than sporadic clear cell RCC and multifocal. Therefore, it is critical to distinguish BHD‐RCC from its sporadic counterparts to identify and monitor affected families and to preserve renal function for as long as possible. The World Health Organization/International Society of Urological Pathology consensus classification defined distinct entities for certain hereditary RCC; however, BHD‐RCC was not included in this classification. Although the clinical features and molecular mechanisms of BHD‐RCC have been investigated intensively over the last two decades, pathologists and urologists occasionally face difficulties in the diagnosis of BHD‐RCC that require genetic testing. Affected patients usually have miscellaneous benign disorders that often precede renal carcinogenesis. In the present review, we summarize the current understanding of the histopathological features of BHD‐RCC based on our epidemiological studies of Japanese families and a literature review. Pathological diagnostic clues and differential diagnosis of BHD‐RCC from other hereditary RCC are also briefly discussed. Abstract : Birt‐Hogg‐Dubé (BHD) syndrome is associated with the development of hereditary renal cell carcinoma. We summarize the current understanding of the histopathological features of BHD syndrome‐associated renal cell carcinoma based on our epidemiological studies of Japanese families and a literature review.